THE IMPORTANCE OF TELEMEDICINE IN MODERN HEALTHCARE SYSTEMS (Global Conference on Medical and Health Sciences, 2026)
Telemedicine has become an essential component of modern healthcare systems, offering innovative solutions to improve access to medical services. This paper examines the role of telemedicine in enhancing healthcare delivery, particularly in remote and underserved areas. It explores the benefits of remote consultations, digital monitoring, and virtual healthcare platforms. The study also discusses challenges such as technological limitations, data privacy, and patient trust. The findings indicate that telemedicine improves efficiency, reduces healthcare costs, and increases accessibility. The paper concludes that telemedicine will continue to play a significant role in the future of global healthcare.
Keywords: telemedicine, remote healthcare, digital health, virtual consultation, healthcare access, patient monitoring, e-health, medical technology.